Comprehensive Algorithmic Review and Analysis of LDPC Codes - Waheed Ullah; Abid Yahya (Institute of Advanced Engineering and Science, 2015)
Due to the increasing popularity of LDPC codes and its demand for future applications, first time in this paper, LDPC coding techniques have been systematically summarized and analyzed. The paper gives the comprehensive review of LDPC encoder, decoder and its architecture for simulation and implementation. The paper is specially intended for giving an insight of the algorithmic overview of the LDPC encoder, decoder and its architecture for research and practical purposes. The original belief propagation algorithm (BPA) , logarithmic model of BPA , and the other simplified form of the logarithmic sum product algorithms (SPA) has been elaborated and analyzed for medium and short length codes under AWGN channel